Unified viscoplasticity modeling for isothermal low-cycle fatigue and fatigue-creep stress–strain responses of Haynes 230. (15th June 2016) - Ahmed, Raasheduddin; Barrett, Paul R.; Hassan, Tasnim
Highlights: A constitutive model for combustor liner material Haynes 230 is developed. A broad set of isothermal low-cycle fatigue and fatigue-creep responses are simulated. Static recovery feature simulated stress relaxation in rate-independent regime. Simulation of mean stress evolution needs additional modeling feature. Strain range modeling features are essential to simulate hysteresis loop shapes. Abstract: A robust cyclic viscoplasticity model is developed for simulating a broad set of isothermal, low-cycle fatigue and fatigue-creep responses of Haynes 230 (HA 230) under uniaxial loading. High temperature components experiencing thermo-mechanical fatigue failures can be designed considering their failure responses such that their fatigue life is predictable. Hence, design of high temperature components in aerospace, automobile, nuclear power, and chemical industries should be based on viscoplastic nonlinear analysis using a robust constitutive model. A unified viscoplasticity model based on the nonlinear kinematic hardening rule of Chaboche with several added features for strain-range dependence, rate-dependence, static recovery, and mean stress evolution is developed and evaluated against a broad set of HA 230 responses. Robustness of the constitutive model is demonstrated against predicting fatigue and dwell period stress relaxation responses under uniaxial strain-controlled loading for a broad temperature range of 25–982 °C and strain rate range of 1.1×10 −2 to 2.6×10 −5 /s. Parameter determination of such an advanced model is discussed showing the importance of a well thought out experimental database and thereby providing physical meaning to model parameters.